ASUHAN KEPERAWATAN GAGAL GINJAL KRONIK PADA NY. S DENGAN MASALAH KEPERAWATAN NYERI OTOT KAKI DENGAN PENERAPAN TERAPI FOOT MASSAGE DI RUANG HEMODIALISIS KLINIK UTAMA KIMIA FARMA SAGULUNG BARU - Afif D Alba (CV. ADIBA AISHA AMIRA, 2024)
Deaths caused by CKD increased by 31.7% over the last 10 years. The increasing number of patients with CRF has led to an increase in the number of patients undergoing hemodialysis which has increased by 8% annually. The problem that often arises in HD patients is acute pain. The prevalence of acute pain in HD patients is around 33% to 86%. One of the non- pharmacological therapies in reducing muscle cramps is the foot massage method. Foot massage therapy is massage on the foot area in a circular motion, squeezing and rubbing to relax the leg muscles and reduce pain in the leg muscles. This professional scientific paper aims to carry out Nursing Care for Chronic Kidney Failure in Ny. S With Leg Muscle Pain with Nursing Problems Application of Foot Massage Therapy in the Hemodialysis Room of the Main Clinic of Kimia Farma Sagulung Baru Batam in 2023. The method used is a case study conducted based on the stages of nursing care including assessment of pain scale 5, main nursing diagnoses Acute pain associated with increased muscle contraction during HD therapy. Intervention and implementation of nursing carried out by applying the foot massage technique for 3 days obtained the results of the final evaluation of nursing care for Mrs. S, the client said cramp pain in the left and right leg muscles as if pulled, the pain scale dropped from 5 to 2, the client seemed to be still massaging his legs, the client saw that if the cramps came, the client did the foot massage technique. The results of the last assessment on March 10, 2023 in 2023 the pain scale dropped to 2 through the foot massage technique can help reduce acute pain. Suggestions for patients with Chronic Renal Failure are doing foot massage techniques so that they can help reduce pain during hemodialysis therapy